IMPROVING POETRY WRITING SKILLS THROUGH A THINK-PLUS STRATEGY USING IMAGES OF EVENTS IN NEWSPAPERS - Azhari; Nurmalawati; Ainol Mardiah (CV. RADJA PUBLIKA, 2024)
This study raises the issue of the low writing ability of class X students at SMK Negeri 3 Lhokseumawe, Lhokseumawe City. The low ability is identified as a result of the implementation of learning to write poetry that has not been optimal, so that students experience difficulties when they have to write poetry. For this reason, it is necessary to apply learning strategies and media that are interesting and in accordance with the needs of students. In this study, the Think Plus strategy and media in the form of pictures of events from newspapers were used as an effort to improve learning to write poetry in class X. The research was conducted through two cycles, where each cycle included planning, action, observation, and reflection stages. The results showed an improvement in the learning process which had an impact on improving students' abilities and changing their behavior in a more positive direction.